Development of Games Book Media in Reading Interest in PKn Learning Class IV Private Elementary School Bakti 1 - Anisya Fitri (Berpusi Publishing, 2025)
This research is a research and development (Research and Development) that produces a product in the form of learning media in the form of Games Book on the material of religious diversity for fourth grade students of Bakti 1 Private Elementary School. This study aims to determine the process of developing Games Book learning media and determine the level of practicality of the developed media. The development model used is the 4D model which includes the Define, Design, Develop, and Disseminate stages, but in this study it was only carried out up to the Develop stage. The development process was carried out through validation by experts, product revisions, and limited trials with students. The validation results showed that the games book learning media received a very valid assessment from media experts of 100% and from material experts of 96.6%. In addition, the results of the practicality test showed a percentage of 84% from students and 96% from teachers. This shows that the developed games book learning media is feasible and practical to use in the learning process of fourth grade students of Bakti 1 Private Elementary School.